Electric field-directed cell shape changes, displacement, and cytoskeletal reorganization are calcium dependent (The Rockefeller University Press, 1988)
C3H/10T1/2 mouse embryo fibroblasts were stimulated by a steady electric field ranging up to 10 V/cm. Some cells elongated and aligned perpendicular to the field direction. A preferential positional shift toward the cathode was observed which was inhibited by the calcium channel blocker D-600 and the calmodulin antagonist trifluoperazine. Rhodaminephalloidin labeling of actin filaments revealed a field- induced disorganization of the stress fiber pattern, which was reduced when stimulation was conducted in calcium-depleted buffer or in buffer containing calcium antagonist CoCl2, calcium channel blocker D-600, or calmodulin antagonist trifluoperazine. Treatment with calcium ionophore A23187 had similar effects, except that the presence of D-600 did not reduce the stress fiber disruption. The calcium-sensitive photoprotein aequorin was used to monitor changes in intracellular-free calcium. Electric stimulation caused an increase of calcium to the micromolar range. This increase was inhibited by calcium-depleted buffer or by CoCl2, and was reduced by D-600. A calcium-dependent mechanism is proposed to explain the observed field-directed cell shape changes, preferential orientation, and displacement.